2018
DOI: 10.1016/j.toxrep.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the anti-diabetic potential of d-ribose-l-cysteine with insulin, and oral hypoglycaemic agents on pregnant rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…Usually, hepatocytes supply GSH that is found in plasma and plasma GSH is kept at low concentration because of metabolism of GSH by many other cells [30]. This makes glutathione to be generally more predominant in animal cells (0.5-10 mmol/L) than in plasma (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) μmol/L) [6,30]. Furthermore, half-life of GSH in tissues varies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, hepatocytes supply GSH that is found in plasma and plasma GSH is kept at low concentration because of metabolism of GSH by many other cells [30]. This makes glutathione to be generally more predominant in animal cells (0.5-10 mmol/L) than in plasma (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) μmol/L) [6,30]. Furthermore, half-life of GSH in tissues varies.…”
Section: Discussionmentioning
confidence: 99%
“…DRLC was also reported to attenuate memory deficit induced by lipopolysaccharide in mice models [ 9 ]. In Sprague-Dawley rats, DRLC administration attenuated reproductive hormones and sperm parameters in aluminium-induced testicular damage [ 10 ], Streptozotocin-induced diabetic rats [ 11 ] and also as an oral hypoglycaemic agent in pregnant-diabetic rats [ 12 ]. Other studies also showed DRLC enhanced wound healing [ 13 ] and halted the progression of intervertebral disc degeneration in rabbits [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrapleura tetraptera treatment shows no significant impact on crown-rump length, foetal and ovarian weight. This is adduced to nutritional bioactive component of the TT on placental barrier to effectively regulate exogenous maternal change ( Blundell et al., 2016 ; Abraham et al., 2018 ). We can therefore, deduce that bioactive constituent of TT is effective and safe in management of pregnancy from first trimester to parturition period which is evidence in weight of placental and empty uterus.…”
Section: Discussionmentioning
confidence: 99%
“…These mating animals were left together overnight. Vaginal lavage was taken on the morning (estrous day of the cycle) following pairing between 8:00–9:00 am The presence of sperm spermatozoa in the lavage was marked as day 1 of pregnancy ( Abraham et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The rats were divided into four groups (n = 8), labeled groups A, B, C, and D. The Arsenic (Mehranjani & Hemadi, 2007) and DRLC dosages (Osinubi et al, 2018) were prepared daily. Group A received normal saline as placebo; Group B was administered with 8mg/kg BW arsenic only; Group C was administered with 8 mg/kg BW arsenic followed by 10 mg/kg BW DRLC (low dose) and Group D were administered with 8mg/kg BW arsenic followed by 30 mg/kg BW DRLC (high dose).…”
Section: Experimental Protocolmentioning
confidence: 99%